Cardiac Emergency Response Planning for Schools: A Policy Statement. (September 2016) - Rose, Kathleen; Martin Goble, Monica; Berger, Stuart; Courson, Ron; Fosse, Gwen; Gillary, Randall; Halowich, Joe; Indik, Julia H.; Konig, Madeleine; Lopez-Anderson, Martha; Murphy, M. Kathleen; Newman, Mary M.; et al.
A sudden cardiac arrest in school or at a school event is potentially devastating to families and communities. An appropriate response to such an event—as promoted by developing, implementing, and practicing a cardiac emergency response plan (CERP)—can increase survival rates. Understanding that a trained lay-responder team within the school can make a difference in the crucial minutes between the time when the victim collapses and when emergency medical services arrive empowers school staff and can save lives. In 2015, the American Heart Association convened a group of stakeholders to develop tools to assist schools in developing CERPs. This article reviews the critical components of a CERP and a CERP team, the factors that should be taken into account when implementing the CERP, and recommendations for policy makers to support CERPs in schools.